(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This study investigates the effectiveness of literature-based instruction and storytelling in teaching English as a foreign language (EFL) to 5th and 6th grade pupils. Grounded in communicative language teaching and constructivist theory, the research evaluates the impact of storytelling on vocabulary acquisition, speaking fluency, and learner engagement. A quasi-experimental design was implemented with 60 participants divided into control and experimental groups. Data were collected through pre- and post-tests, observation protocols, and motivation questionnaires. Statistical analysis revealed significant improvements in vocabulary and speaking performance in the experimental group (p < 0.05). Qualitative findings indicate increased engagement, confidence, and classroom interaction. The study concludes that storytelling and literary texts provide an effective pedagogical framework for enhancing communicative competence among young EFL learners and recommends their systematic integration into primary education curricula.